Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Karyawan PT. Aron Logistik - Marsofiyati Marsofiyati; Dian Zahwa Oktaviani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
Compensation is a form of reward given by the company to employees as appreciation for their contribution to work, both in financial and non-financial forms. Compensation can encourage better employee performance, as they feel valued for what they have done for the company. However, it is not only compensation that can trigger good employee performance, but motivation also plays an important role in driving employee performance. Motivation is a process that arises from an individual's psychological factors, which then directs and determines the individual's actions towards achieving their goals. This psychological drive can encourage employees to strive hard to achieve their goals, be it personal goals or common goals within a company. This research uses a causal quantitative approach with a survey method, and the data is processed using SPSS. The results of the study show that compensation and motivation play a very important role in improving the performance of employees at PT. Aron Logistics Jakarta.